Neuroinflammation in Neurology and Psychiatric Disorders, Mechanisms, Challenges and Emerging Therapeutic Strategies - Sharma, Siddharth; H, Harshita (Journal of Pharmacy Practice and Community Medicine)
Neuroinflammation has emerged as a pivotal process underlying a wide spectrum of neurological and psychiatric disorders. Unlike peripheral immune responses, inflammation within the central nervous system involves a tightly regulated interplay between resident immune cells, such as microglia and astrocytes, and molecular signaling pathways uniquely adapted to the brain’s microenvironment. This paper explores the multifaceted mechanisms that initiate and sustain neuroinflammation, highlighting key cellular and molecular mediators including cytokines, chemokines, and the complement system. Disruption of the Blood–Brain Barrier, immune cell infiltration, and chronic microglial activation are examined as central contributors to disease progression. Current therapeutic approaches, including non-steroidal anti-inflammatory drugs, corticosteroids, and disease-modifying agents for multiple sclerosis, are critically reviewed in the context of their effectiveness and limitations. The paper further discusses emerging therapies aimed at microglial modulation, inflammasome inhibition, and oxidative stress reduction. Emerging approaches such as stem cell therapies, RNA-based medications, and targeted drug delivery systems represent promising directions for future treatment. Refinements in our understanding of immune mechanisms within the central nervous system are paving the way to more targeted and effective approaches for treating neuroinflammatory conditions.
Keywords: Neuroinflammation; Central nervous system; Microglia; Blood–brain barrier; Cytokines; Neurodegenerative disorders; Psychiatric Illness; Anti-inflammatory Therapy; Microglial Modulation; Emerging Therapeutics